Pollination ecology of the Cerrado species Eschweilera nana (Lecythidaceae subfam. Lecythidoideae) - de Moraes de Potascheff, Carolina [UNESP]; Mori, Scott A.; Lombardi, Julio Antonio [UNESP] (Springer Nature, 2013)
Eschweilera nana is pollinated by a guild of pollinators consisting of mostly bees. Effective pollinators are large bees able to force their way into the closed androecium to access nectar. The morphology of the flowers diminishes self pollination and promotes cross-pollination. Although many pollinators make diurnal visits to the flowers, fruit set was very low in comparison with the number of flowers produced. Breeding system tests yielded only two fruits, one produced by xenogamy and another one in the control test. The results of this study are consistent with studies of other Cerrado plants pollinated by guilds of insects and support the conclusion of other pollination studies of Lecythidaceae that fruit set is low in comparison with the high numbers of flowers produced. © 2013 The New York Botanical Garden.
Keywords: Barra do Garças; bee pollination; Campsomeris; Parque Estadual da Serra Azul; pollination biology